Key drivers regulating arsenic enrichment in shallow groundwater of the Pearl River Delta: Comprehensive analyses of iron, competitive anions, and dissolved organic matter. (April 2023) - Yi, Hulong; Cui, Jinli; Sun, Jianteng; Zhou, Xingyu; Ye, Tiancai; Gan, Shuchai; Chen, Jingcheng; Yang, Yuzhong; Liang, Weixin; Guo, Pengran; Abdelhaleem, Amal; Xiao, Tangfu
Abstract: Arsenic (As) contamination in groundwater is a global environmental geochemical problem that threatens over 100 million people around the world. Although groundwater As enrichment has been demonstrated to result from some major complex processes, including competitive desorption by anions and reductive release of As from iron (Fe) oxyhydroxides due to microbial respiration of dissolved organic matter (DOM), knowledge of the detailed interactions among these processes and their respective contributions is still limited. In this study, we aimed to elucidate the key variables that regulate the evolution of dissolved As in shallow groundwater from a typical As-contaminated region of the Pearl River Delta (PRD) after comprehensive statistical analysis of hydrogeochemical characteristics. The results showed that the highest concentration of As in the groundwater samples (n = 77) was 57 μg/L, with 9% of samples exceeding the drinking water standard. In comparison with other regions with geogenic As contamination in groundwater, the relatively low As concentration range is primarily controlled by the well-oxygenated environment, which also contributed to the dominance of As(V) (19.5–100.0%, median of 100.0%). Hierarchical cluster analysis (HCA) and principal component analysis (PCA) suggested that the presence of As in groundwater may be impacted by the reduction process of Fe/Mn oxyhydroxides and by competitive anions. Further analysis using structural equation modeling (SEM) indicated that the increased concentration of As(V) in the shallow groundwater was primarily induced by the competitive roles of phosphate and silicate, explaining 65.2% and 31.5% of total As(V), respectively. In contrast, the presence of As(III) was strongly explained by DOM (23.8%, 12.4%, and 5.7% from microbial humic-like, terrestrial humic-like, and protein-like components, respectively) and Fe (31.8%), followed by competitive desorption (26.3%), revealing the dominant contribution from DOM-facilitated Fe reduction to As(III) enrichment. Our study empirically demonstrated that decreasing the concentrations of phosphate and reactive organic matter can effectively alleviate As contamination in groundwater. Graphical abstract: Image 1 Highlights: Phosphate, Fe reduction, and organic matter trigger As release in PRD groundwater. As species in As(V)-dominated groundwater are controlled by the oxidizing environment. Phosphate and silicate contributed substantially to the competitive desorption of As(V). Release of As(III) is probably facilitated by iron (oxyhydr)oxide reduction. Increased As(III) was related to increasing microbial humic-like components.